The hepatitis C virus (HCV) protein, p7, suppresses inflammatory responses to tumor necrosis factor (TNF)-α via signal transducer and activator of transcription (STAT)3 and extracellular signal-regulated kinase (ERK)-mediated induction of suppressor of cytokine signaling (SOCS)3 - Stevenson, Nigel; O'Farrelly, Cliona (My University, 2019)
Viruses use a spectrum of immune evasion strategies that enable infection and replication. The acute phase of hepatitis C virus (HCV) infection is characterized by nonspecific and often mild clinical symptoms, suggesting an immunosuppressive mechanism that, unless symptomatic liver disease presents, allows the virus to remain largely undetected. We previously reported that HCV induced the regulatory protein suppressor of cytokine signaling (SOCS)3, which inhibited TNF-a–mediated inflammatory responses. However, the mechanism by which HCV up-regulates SOCS3 remains unknown. Here we show that the HCV protein, p7, enhances both SOCS3 mRNA and protein expression. A p7 inhibitor reduced SOCS3 induction, indicating that p7’s ion channel activity was required for optimal up-regulation of SOCS3. Short hairpin RNA and chemical inhibition revealed that both the Janus kinase–signal transducer and activator of transcription (JAK-STAT) and MAPK pathways were required for p7-mediated induction of SOCS3. HCV-p7 expression suppressed TNF-a–mediated IkB-a degradation and sub- sequent NF-kB promoter activity, revealing a new and functional, anti-inflammatory effect of p7. Together, these findings identify a molecular mechanism by which HCV-p7 induces SOCS3 through STAT3 and ERK activation and demonstrate that p7 suppresses proinflammatory responses to TNF-a, possibly explaining the lack of in- flammatory symptoms observed during early HCV infection.—Convery, O., Gargan, S., Kickham, M., Schroder, M., O’Farrelly, C., Stevenson, N. J. The hepatitis C virus (HCV) protein, p7, suppresses inflammatory responses to tumor necrosis factor (TNF)-a via signal transducer and activator of transcription (STAT)3 and extracellular signal-regulated kinase (ERK)–mediated induction of suppressor of cytokine signaling (SOCS)3.
PUBLISHED
Keywords: inflammation; viral immune evasion; intracellular signaling pathways; immune regulation; JAK-STAT signalling pathway; Immunology, Inflammation & Infection